Disinfection of therapeutic water – balancing risks against benefits: case study of Hungarian therapeutic baths on the effects of technological steps and disinfection on therapeutic waters. (14th December 2021) - Gere, Dóra; Róka, Eszter; Erdélyi, Norbert; Bufa-Dőrr, Zsuzsanna; Záray, Gyula; Vargha, Márta
Abstract: Thermal therapeutic pools in most countries are operated in a manner similar to swimming pools: with water circulation, filtration and disinfection. However, in some countries, including Hungary, therapeutic pools are traditionally not treated this way, in order to preserve the therapeutic qualities of the water. However, dilution and frequent water replacement applied in these pools are often insufficient to ensure adequate microbial water quality, posing a risk of infection to the bathers. In the present case study, the impact of water treatment (including chemical disinfection by hypochlorite or hydrogen peroxide) was investigated on the therapeutic components of the water in seven Hungarian spas of various water composition. Microbial quality was improved by both disinfectants, but hypochlorite reduced the concentration of the therapeutic components sulfide, bromide, and iodide ions by 40–99%, and high levels of disinfection by-products were observed. Hydrogen peroxide only affected sulfide ion (91% reduction). Other technological steps (e.g., transport or cooling by dilution) were found to have significant impact on composition, often outweighing the effect of disinfection. The current case study demonstrated that thermal waters may be treated and disinfected with minimal loss of the therapeutic compounds, if an adequate treatment procedure is selected based on the water composition. HIGHLIGHTS: Disinfection of therapeutic pools is necessary to maintain adequate water quality. Due to the diversity of therapeutic waters, there is no universal method of disinfection. Hypochlorite reduce concentration of therapeutic components sulfide, bromide and iodide ion. Hydrogen-peroxide reduce only concentration of sulfide ion. Health gain from better microbial quality is likely to counteract the loss of therapeutic effect.